Proteomic and metabolomic profiling reveals the underlying molecular mechanisms in modified alternate-day fasting-mediated protection against Diabetic kidney disease - Xin Zeng; Yi-hang Xing; Xiu-mei Ma; Yang Long; Zong-zhe Jiang; Yong Xu (PLoS ONE, 2025)
Background Diabetic kidney disease (DKD) is a leading cause of chronic kidney disease, and while lifestyle interventions like intermittent fasting have shown promise in treating diabetes, the impact of modified alternate-day fasting (MADF) on DKD is not well understood. This study aimed to explore MADF’s effects on DKD in db/db mice, a model for the condition, and to investigate its underlying mechanisms. Methods We implemented an MADF regimen in db/db mice on a high-fat diet, measuring blood glucose, body weight, and renal function at various times. After the intervention, we analyzed the proteome and metabolome of renal tissues. Results MADF was found to reduce hyperglycemia and slow the pathological progression of DKD in the mice. Proteomic analysis identified 165 proteins that increased and 196 that decreased in the kidneys of db/db mice compared to controls. MADF intervention led to a decrease in 26 of the increased proteins and an increase in 18 of the decreased ones. Notably, many of these proteins, including cathepsin S (CTSS), were related to lysosomes, suggesting a role in renal protection. Metabolomic profiling revealed changes in metabolites associated with inflammation, such as prostaglandin A1, which was downregulated in db/db mice and upregulated with MADF. Western blotting, immunohistochemistry, and immunofluorescence staining confirmed the expression changes of CTSS observed in the proteomic data. Additionally, CTSS expression was found to increase in renal cells exposed to high glucose and palmitic acid. Conclusion MADF appears to mitigate the progression of DKD, with proteomic evidence pointing to lysosome-related proteins like CTSS as potential mediators of its renal protective effects. These findings indicate that MADF and the inhibition of CTSS could be considered as novel therapeutic strategies for DKD treatment.